Impact of the Environment on Health - Juntarawijit, Chudchawal (Journal of Health Science of Thailand, 2018)
This article described the relationship between environment and health and presented data on health problems that relate to the environment, collected by the World Health Organization. From data analysis of causes of disease groups, it was found that there were 102 disease groups and 85 disease groups were related to the environment. The top 4 diseases that were influenced by the environment were diarrhea, lower respiratory infections, unitentional injuries, and malaria. Furthermore, the data showed that children experienced the highest impact from diseases related to the environment. As such, children aged under 5 years loss of average healthy life years was 5 times compared to that of the general population. The data revealed that the environment had high impact on health. Therefore, all related organizations should be concerned about these issues because illness and death can be prevented by good environmental management.